NILAI PENDIDIKAN ISLAM DALAM TRADISI BROKOHAN MASYARAKAT DESA KRAMATTEMENGGUNG, SIDOARJO - Choirun Nisa (LPPM Universitas Uluwiyah Mojokerto, 2025)
This article examines Islamic educational values embedded in the Brokohan tradition as a form of local wisdom practiced by the community of Kramattemenggung Village, Sidoarjo Regency. The study aims to analyze the values of Islamic education related to faith (aqidah), Islamic law (shari’ah), and morality (akhlaq) internalized in the Brokohan ritual as a cultural practice celebrating childbirth. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The data were analyzed inductively and validated using source triangulation. The findings indicate that the Brokohan tradition embodies Islamic educational values that contribute to religious character formation, particularly through the inculcation of monotheism, observance of Islamic practices, and moral cultivation. The tradition serves as a cultural-educational medium integrating Islamic teachings with local cultural expressions.